Black Nationalism in the New World : Reading the African-American and West Indian Experience - Carr, Robert, 1963-2011 (Book collections on Project MUSE., 2002)
Provides new insight into the development of black nationalism by examining the intersection of African-American and West Indian nationalist literatures.